Practical recommendations for the use of ACE inhibitors, beta-blockers and spironolactone in heart failure: putting guidelines into practice. - McMurray, J; Cohen-Solal, A; Dietz, R; Eichhorn, E; Erhardt, L; Hobbs, R; Maggioni, A; Pina, I; Soler-Soler, J; Swedberg, K (2001)
Surveys of prescribing in both hospitals and primary care have shown delays in translating improved survival data from clinical trials into clinical practice thereby denying patients the benefits of proven treatments, such as the angiotensin converting enzyme inhibitors. This may be due to unfamiliarity with clinical guidelines and concerns about adverse events. Recent trials have shown that substantial improvements in survival are associated with spironolactone and beta-blocker therapy. In order to accelerate the uptake of these treatments, and to ensure that all eligible patients should receive the most appropriate medications, a clear and concise set of clinical recommendations has been prepared by a group of clinicians with practical expertise in the management of heart failure. The objective of these recommendations is to provide practical guidance for non-specialists in order to support the implementation of evidenced-based therapy for heart failure. These practical recommendations are meant to supplement rather than replace existing guidelines.